El Excentrico, 1975-01-20 - Garcia, Bert:::Publisher::::::::::::; Garcia, Marc:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
January 20, 1975. [20 de enero de 1975]. No volume or issue number. Cover has advertisement for Muebles Hacienda, a home furnishing store on First Street in San Jose, California.